Epidemiological Investigations on Cystic Echinococcosis in North-West (Sidi Kacem Province) Morocco: Infection in Ruminants. (19th April 2015) - El Berbri, Ikhlass; Petavy, Anne Françoise; Umhang, Gerald; Bouslikhane, Mohammed; Fassi Fihri, Ouafaa; Boué, Franck; Dakkak, Allal
Abstract : Despite alarming statistics on cystic echinococcosis (CE) in humans and the importance of dog and ruminant populations, no epidemiological investigations have been performed on CE in Sidi Kacem Province (North-West of Morocco). A part of large research project was devoted to determine the status of CE in ruminants. This paper reports the results of the investigations carried out in the 10 abattoirs of this region, over four successive years (April 2009–March 2013). A total of 1, 302 sheep, 652 head of cattle, and 136 goats were postmortem examined and hydatid cysts were collected and examined. The overall CE prevalence of infection was 42.9% in cattle, 11.0% in sheep, and 1.5% in goats. The prevalence shows significant association with age in sheep and cattle; sheep above 3 years and cattle above 5 years are highly infected (64.0% and 72.2%, resp.). Only liver and lungs are found to be infected. Molecular analyses identified G1, G2, and G3 of E. granulosus sensu stricto in liver and lung samples. Cyst fertility was significantly higher in sheep (54.9%) than in cattle (50.3%). These findings suggest that control measures should target not only sheep but also cattle.